Factors that influence employee retention at Perkeso Johor Bahru / Muhammad Nasrulhaziq Zaa’ba - Zaa’ba, Muhammad Nasrulhaziq (Faculty of Business and Management, 2019)
The research objective was to investigate whether factors that influence employee retention which include rewards and compensation, training and development, career development and work environment have a positive relationship with employee retention. The target respondents in this study were employees who work in Pertubuhan Keselamatan Sosial (PERKESO) Johor Bahru. The collected data were analysed using Statistical Package for Social Science (SPSS) software. The data was collected and a percentage of 72 percent was achieved out of the possible 165 respondents which was derived from the total population of 290 employees. Descriptive analysis, reliability test, correlation analysis and multiple regressions were used to analyse the collected data. The study showed that there are positive effects towards employee retention which includes rewards and compensation, training and development, career development and work environment.